2017
DOI: 10.1016/j.riem.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Publicación desde el pregrado en Latinoamérica: dificultades y factores asociados en estudiantes de Medicina

Abstract: Introducción: La enseñanza de investigación científica durante el pregrado representa un pilar fundamental en el desarrollo integral del estudiante, que debe ser una prioridad en todas las universidades.Objetivo: Identificar factores asociados a la publicación científica en estudiantes de Medicina de Latinoamérica. Método: Estudio descriptivo de corte transversal. Los participantes de un curso extracurricular dirigido por una sociedad científica respondieron continuamente durante 8 semanas a unos cuestio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
14

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 15 publications
1
8
0
14
Order By: Relevance
“…However, conducting research at this educational stage is difficult due to limitations such as a lack of counseling, proper time management, inadequate curriculum and the inflexibility of some courses, among others. [1][2][3] Despite the relevance of teaching and practice of research within the undergraduate level, both currently face serious difficulties in terms of quantity and quality. 4,5 The number of graduates that pursue a career in research have decreased in Latin America and globally.…”
Section: Introductionmentioning
confidence: 99%
“…However, conducting research at this educational stage is difficult due to limitations such as a lack of counseling, proper time management, inadequate curriculum and the inflexibility of some courses, among others. [1][2][3] Despite the relevance of teaching and practice of research within the undergraduate level, both currently face serious difficulties in terms of quantity and quality. 4,5 The number of graduates that pursue a career in research have decreased in Latin America and globally.…”
Section: Introductionmentioning
confidence: 99%
“…Chile es uno de los países de la región con mayor número de publicaciones científicas en el área de la salud y ocupa un lugar importante en producción científica estudiantil en Latinoamérica (2,3) . Sin embargo, la producción científica estudiantil se concentra fuertemente en estudiantes de medicina por encima de las otras áreas de las ciencias de la salud, por lo que se hace menester incrementar la participación de otros estudiantes.…”
Section: Introductionunclassified
“…On the contrary, an excessive teaching load is highlighted as having a negative impact on research. [5][6][7] Some teachers highlight that the lack of access to databases, work overload, and lack of economic incentives prevents them from devoting themselves to scientific research and production. 8 Pasache et al, 9 when studying the cases of 34 professors, found that 66,7% did not publish in journals or participate in congresses.…”
Section: Introductionmentioning
confidence: 99%